پیر محمد کرم شاہ الازہر ی کا مطالعۂ استشراق: ایک تحقیقی جائزہ: Pīr Muhammad Karam Shah Al-Azharī’s Study of Orientalism: A Research Review - Hafiz Ghulam Ghaus; Dr. Arshad Munir (Al-Qamar, 2020)
One of the prominent contemporary Islamic scholars who have done significant works on Orientalism is Pīr Muhammad Karam Shah Al-Azharī. This article studies his efforts in the referred perspective with special reference to his prominent writing on Sīrah named “Ziā al-Nabī”. It finds that the last two volumes of this work critically and carefully examine the theories of the Orientalists about Quran, Ḥadīth and Sīrah. Al-Azharī stated the goals of the Orientalists and described the way in which they propagate their ideas. The study highlights that Al-Azharī’s attitude while studying the works of orientalists has been scientific and systematic. He has successfully responded all the objections of the orientalists especially regarding the personality and character of Prophet Muhammad (ﷺ).